Efek Pernikahan Dini: Sebuah Pertimbangan Bahaya Sosial dan Kesehatan - Suryadilaga, Muhammad Alfatih (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
The phenomena of child marriages have been assumed to have significant correlation with patriarchal society and culture which is characterized by gender biases. Many today's communities who endorse child marriages are still ignorant of the negative impacts of such child marriages. Many studies have showed that child marriages have resulted in unwanted pregnancy, unsafe abortion, high number of divorce, human trafficking, as well as unemployment. This article argues ihat child marriage may not only endanger the physical wellbeing of the brides, but also their mental and social health.